Social responsibility in Ukrainian agriculture: the regional issue - Larysa Levkivska; Inna Levkovych (Eastern Journal of European Studies, 2017)
The social responsibility of agribusiness is currently one of the highly debated issues. Factors such as the globalization of agri-food supply chains, increasing competition, further integration of Ukraine in Europe and the world market, developments of Ukrainian large scale farms as well as public pressure on farms make the analysis of Corporate Social Responsibility (CSR) highly relevant to Ukrainian agribusiness. The paper provides insights on the understanding of CSR by the Ukrainian agricultural enterprises, CSR activities implemented by farms and main drivers encouraging the implementation of CSR initiatives. The analysis is based on literature reviews and questionnaires of Ukrainian agricultural enterprises and representatives of the local community in Oblasts Zhytomyr, carried out in spring 2016.
Keywords: 330; corporate social responsibility; agriculture; agribusiness; agroholdings; rural development; Ukraine